2008
DOI: 10.1681/asn.2007040513
|View full text |Cite
|
Sign up to set email alerts
|

Acute Rejection Modulates Gene Expression in the Collecting Duct

Abstract: Kidney transplantation, especially when associated with acute rejection, leads to changes in the expression of many genes, including those encoding solute transporters and water channels. In a rat model of acute rejection after allogeneic renal transplantation, impaired renal function, increased urine volume, and increased fractional excretion of sodium were observed. Gene array analysis revealed that these findings were associated with significant downregulation of water channels (aquaporin-1, -2, -3, and -4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Grafts were recovered on postoperative day 1, 4, or 7 after transplantation. The chosen aTX model leads to histologic and functional changes typical of acute rejection (19,20). Syngeneically transplanted (sTX) rats (Lewis-brown Norway to Lewis-brown Norway) and aTX rats treated with cyclosporine A (CSA, 5 mg/kg of body weight/d intraperitoneally) since transplantation (postoperative day 0) without allograft rejection served as controls.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Grafts were recovered on postoperative day 1, 4, or 7 after transplantation. The chosen aTX model leads to histologic and functional changes typical of acute rejection (19,20). Syngeneically transplanted (sTX) rats (Lewis-brown Norway to Lewis-brown Norway) and aTX rats treated with cyclosporine A (CSA, 5 mg/kg of body weight/d intraperitoneally) since transplantation (postoperative day 0) without allograft rejection served as controls.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Studies in this field show that AQP2 abundance-along with several other key transporters in the distal nephron-is decreased in animal models of acute graft rejection [44]. These effects are consistent with tubular damage induced by the stimulated immune system and are known to be ameliorated or even reversed by calcineurin inhibitor treatment [8,9].…”
Section: Discussionmentioning
confidence: 65%
“…In this study we identified discrepancies in the current histological recognition of stable allografts and demonstrated a new Instability Score (or InstaScore), a linear combination of selected features based on the input from tissue gene expression and inferred cell type biopsy molecular data modeled on AR biology, that provides precise (sub-)phenotyping and early recognition of molecular and cellular rejection of otherwise functionally and histologically stable allografts on protocol biopsies. Unlike other published studies by others [61][62][63][64][65] and our group [2,54,66,67] that have only studied gene expression transcriptional perturbation in AR, this is the first development and application of a combined genes and cell types into Instability Score in tissue that can rapidly reclassify samples into molecularly and even more importantly, functionally relevant, diverse groups: those most similar to the normal kidneys (hSTA/mSTA) and those most similar to the rejected kidneys (hSTA/mAR).…”
Section: Discussionmentioning
confidence: 90%